Current Ratio (CR), Earning Per Share (EPS), dan Pengaruh Return on Assets (ROA) terhadap Stock Price pada Perusahaan Sub Sektor Kesehatan Terdaftar di Bursa Efek Indonesia (BEI) 2019 - 2023 - Setiawan, Fendik Alex; Indarto, Muhammad Roni (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2025)
The purpose of this research is to investigate the simultaneous and partial effects of the variables Return on Assets (ROA), Earnings Per Share (EPS), and Current Ratio (CR) on the stock prices of health-related enterprises on the Indonesia Stock Exchange between 2019 and 2023. The independent variables are ROA, EPS, and CR, and the dependent variable is the stock price. Purposive sampling was used in this study, with 16 businesses selected as research samples. Secondary data from https://www.idx.co.id/id, including stock prices and financial statements, was used. The quantitative data analysis methodology for this study makes use of a multiple linear regression model. The analysis concludes that CR, EPS, and ROA have a substantial impact on stock prices simultaneously based on the F-test result, with a probability value of 0.000000 < 0.05. The ROA variable significantly impacts stock prices, with a probability value of 0.0014 < 0.05. According to a likelihood value of 0.2964 > 0.05, EPS has no significant effect on stock prices. CR has a considerable effect on stock prices, with a likelihood value of 0.0033 < 0.05.